Presence of nests and fruits associated with Lutzomyia in the Cocha Cashu Biological Station - Manu National Park, Madre de Dios, 2018 - Neyra-Salazar, Kimberly (2020)
Introduction: Leishmaniasis is a zoonotic parasitic disease of high prevalence in tropical and subtropical regions of the world. In the Peruvian jungle, hosts have not yet been clearly established. In order to understand the dynamics of the disease it is necessary to know the dynamics of wild and anthropophilic Lutzomyia, their habits and behavior. The objective of our study was to determine if the presence of Lutzomyia sp was associated with nests and fruits at the Cocha Cashu Biological Station. Material and Methods: A cross-sectional study was conducted to evaluate the association between the presence of Lutzomyia adults and the presence of nests and fruits available on the ground at Cocha Cashu Biological Station (EBCC) during November 2018. The evaluation of the presence of Lutzomyia was carried out every 25m of walking distance starting from the EBCC buildings at 8:00-13:00 hours. In addition, mosquitoes were captured with a single manual aspirator and identified with taxonomic keys. Results: A manual aspirator was used to perform 955 inspections in which Lutzomyia was found in 14.8% (n = 141), being present 125% more times in trails with nests (PR: 2.25, IC95%: 1.59 - 3.19) and 70% in trails with fruits (PR: 1.7, IC95%: 1.21 - 2.39) . Conclusions: During November 2018, the presence of Lutzomyia on the trails of the Cocha Cashu Biological Station (EBCC) was 14.8% (n=141). Likewise, the presence of nests and fruits increases the probability of finding Lutzomyia in the trails of the EBCC.